Functional interactions between matrix metalloproteinases and glycosaminoglycans. (8th March 2013) - Tocchi, Autumn; Parks, William C.
<x xml:space="preserve">Abstract</x> Similar to most proteinases, matrix metalloproteinases (MMP) do not recognize a consensus cleavage site. Thus, it is not surprising that, in a defined in vitro reaction, most MMPs can act on a wide range of proteins, including many extracellular matrix proteins. However, the findings obtained from in vivo studies with genetic models have demonstrated that individual MMPs act on just a few extracellular protein substrates, typically not matrix proteins. The limited, precise functions of an MMP imply that mechanisms have evolved to control the specificity of proteinase:substrate interactions. We discuss the possibility that interactions with the glycosaminoglycan chains of proteoglycans may function as allosteric regulators or accessory factors directing MMP catalysis to specific substrates. We propose that understanding how the activity of specific MMPs is confined to discreet compartments and targeted to defined substrates via interactions with other macromolecules may provide a means of blocking potentially deleterious MMP‐mediated processes at the same time as sparing any beneficial functions.